Syphilis Infection Markers Among HIV Positive Individuals In The Mexico City HIV/AIDS Program - Luis Alfredo Juárez-Figueroa; Felipe Javier Uribe-Salas; Galileo Vargas-Guadarrama; Andrea González-Rodríguez; Verónica Ruíz-González; Yazmín Medina-Islas; Pilar Hernández-Nevares; Patricia Iracheta-Hernández (Instituto Nacional de Salud Pública, 2020)
Objective: The aim of this study is to evaluate the prevalence of T. pallidum infection markers in HIV-positive individuals receiving highly active antiretroviral therapy (ART) in the Mexico City HIV/AIDS Program, as well as predictive characteristics. Methods: The reverse serologic algorithm method was used for the T. pallidum diagnosis, and applied to 2,383 HIV-positive individuals. Socio-demographic characteristics, sexual practices, previous syphilis diagnosis, and length of antiretroviral treatment, were evaluated. Variables significantly associated with syphilis markers were analyzed using a logistic regression model. Results: Prevalence of "active or resolved" and "probable active" infection markers were 44.2% and 28.8%, respectively. Predictive factors were: Clinic Specialized Condesa Iztapalapa (CECI), previous syphilis diagnosis, MSM, and receptive sex practices. Conclusions: The prevalence of T. pallidum infection markers was the highest ever reported in Mexico, and was related to specific sexual practices as well as previous syphilis diagnosis, elements which require preventive measures in the Mexico City HIV/AIDS Program.